Inhibition of the self-renewal capacity of blast progenitors from acute myeloblastic leukemia patients by site-selective 8-chloroadenosine 3',5'-cyclic monophosphate. - Pinto, A (1992)
The physiologic balance between the two regulatory subunit isoforms, RI and RII, of cAMP-dependent protein kinase is disrupted in cancer cells; growth arrest and differentiation of malignant cells can be achieved when the normal ratio of these intracellular signal transducers of cAMP is restored by the use of site-selective cAMP analogs. In this study we evaluated the effects of the site-selective cAMP analog 8-chloroadenosine 3',5'-cyclic monophosphate (8-Cl-cAMP) on clonogenic growth of blast progenitors from 15 patients with acute myeloblastic leukemia and 3 patients affected by advanced myelodysplastic syndrome. Leukemic blast progenitors undergo terminal divisions, giving rise to colonies in methylcellulose. The self-renewal capacity of blast progenitors is conversely reflected in a secondary methylcellulose assay after exponential growth of clonogenic cells in suspension cultures. In all the samples tested, 8-Cl-cAMP, at micromolar concentrations (0.1-50 microM), suppressed in a dose-dependent manner both primary colony formation in methylcellulose and the recovery of clonogenic cells from suspension culture. Strikingly, in the samples from the entire group of patients, 8-Cl-cAMP was more effective in inhibiting the self-renewing clonogenic cells than the terminally dividing blast cells (P = 0.005). In addition, in four out of six cases studied, 8-Cl-cAMP was able to induce a morphologic and/or immunophenotypic maturation of leukemic blasts. An evident reduction of RI levels in fresh leukemic cells after exposure to 8-Cl-cAMP was also detected. Our results showing that 8-Cl-cAMP is a powerful inhibitor of clonogenic growth of leukemic blast progenitors by primarily suppressing their self-renewal capacity indicate that this site-selective cAMP analog represents a promising biological agent for acute myeloblastic leukemia therapy in humans.